Classic psychedelics do not affect T cell and monocyte immune responses - Rudin, Deborah; Areesanan, Alexander; Liechti, Matthias E.; Gründemann, Carsten (Frontiers in Psychiatry, 2023)
Introduction Classic psychedelics have been shown to exert therapeutic potential for the treatment of various psychiatric disorders, neuropsychiatric diseases, and neuronal damage. Besides their psychopharmacological activity, psychedelics have been reported to modulate immune functions. There has thus far been a sparse exploration of the direct immune-modulating effect of psychedelics on human immune cells in vitro. Since T cells are key mediators of several immune functions, inhibition of their function would increase the risk of infections. Methods We investigated the effect of the classic psychedelics lysergic acid diethylamide (LSD), psilocin, N,N-dimethyltryptamine (DMT), and mescaline on the proliferation and stimulated cytokine release of primary human T lymphocytes and on the stimulated NF-κB induction of monocytes. Results We did not observe any relevant direct immune-modulatory effects of the tested classic psychedelics in either cell line. Discussion We concluded that LSD, psilocin, DMT, or mescaline did not directly stimulate the proliferation or cytokine secretion of primary human T lymphocytes or stimulate NF-κB induction of monocytes. Our findings support the future safe use of classic psychedelics in assisted psychotherapy in patients with life-threatening diseases where immune suppression and diminished immune function would be detrimental.